The Liver as Another Possible Target Organ for Bacillus cereus Infection - Mario Alessandri-Bonetti; Umberto Vespasiani-Gentilucci; Giacomo Luppi; Silvia Angeletti; Giordano Dicuonzo; Antonio Picardi (Case Reports in Infectious Diseases)
A case of liver abscess due to Bacillus cereus infection in an immunocompetent 59-year-old man is reported. Percutaneous drainage and antimicrobial therapy, with vancomycin and levofloxacin afterwards, have been demonstrated to be an appropriate treatment, leading to clinical and radiological cure.